Growth performance and yield of lowland rice variety (MR220CL and MR 263), cultivated in different soil type of Sarawak - Nor Farahin, Zainal Abiddin (Universiti Malaysia Sarawak (UNIMAS), 2015)
Different type of soils has different characteristic, structure and nutrient availability which can cause differences in growth performance and yield of rice (Oryza sativa). Sarawak have cultivated the rowland rice but there are several issue on performance of lowland rice in Sarawak due to the soil condition such as high salinity, poor drainage which cause water clogging during rainy season and intrusion of seawater which caused high salinity to rice cultivation. The pot experiment has been conducted with the 40 replicated in total. The soil that used in this study is the common soil used for rice cultivation in Sarawak which is Gley soils from Bijat series and Grey-White Podzolic soils from Saratok series. MR220CL and MR263 rice variety were used in this study because they are the most common high yielding rice varieties in Peninsular Malaysia. Assessment on the growth performance and the yield of the rice plant were taken based on the parameter such as the culm height, number of tillers and panicles per plant, root shoot ratio, number of filled spikelet, 1000grain weight and grain yield. From the stud)', it was observed that the growth performance and the yield of the rice plant were better in the Glay soils compared to the Grey White Podzolic soils. In the growth performance it shows that the MR220CL have better growth performance compared to MR263 because it have higher culm height and higher number of tillers and panicles per plant. Meanwhile for the yield it shows that MR263 have a better yield compared to MR220CL with the total grain yield of 2800 kg/hectare. However, from the result it can be conclude that the lowland rice (MR220CL and MR263) are not suitable to be cultivated in the soil type of Sarawak because it show a huge reduction in yield as compared to the yield of both variety in Peninsular Malaysia.